Internet of Things (IoT) Cloud Platform Using MQTT End-to-Cloud Architecture - Bakhtiar, Fariz Andri; Habibi, Moh. Wildan; Bhawiyuga, Adhitya; Basuki, Achmad (Journal of Information Technology and Computer Science, 2021)
IoT devices are constrained in computation and storage, therefore cannot store all long-term obtained data or perform complex computations. Shifting those jobs to cloud platform are feasible, yet rising heterogeneity and security issues. This study proposes an IoT cloud platform to facilitate communication among heterogeneous devices and the cloud while ensuring devices’ validity. It uses publish/subscribe paradigm with an end-to-cloud architecture and HTTP-based auth server. The proposed system has successfully addressed heterogeneity and security issues. Performance tests conclude that the fewer publishers publish data simultaneously, the smaller the delay. Moreover, the system performs better at up to 250 publishers as the average delay is under 1000 ms, compared to 500 publishers that has average delay above 1000 ms. On its scalability, in 250-concurrent-publishers experiment, the system affords 191 publishers responded in under one second with 100% success rate. In 500-concurrent-publishers one, 187 responded in under one second with 99% rate.